ACCOUNTING STUDENT’S LEARNING APPROACHES AND IMPACT ON ACADEMIC PERFORMANCE - Ismail, Suhaiza (UI Scholars Hub, 2009)
The objective of the study is threefold. Firstly, the study explores the learning approaches adopted by students in completing their Business Finance. Secondly, it examines the impact that learning approaches has on the student’s academic performance. Finally, the study considers gender differences in the learning approaches adopted by students and in the relationship between learning approaches and academic performance. The Approaches and Study Skills Inventory for Students (ASSIST) was used to assess the approaches to learning adopted by students whilst the students final examination result was considered in examining the performance of the students. The results indicate that majority of the accounting students, both male andfemale groups prefer to use the deep approach in studying Business Finance. The findings also reveal that there were significant relationships between learning approaches and academic performance with positive direction appears for deep and strategic approaches whilst negative relationship reveals for surface approach.